Spleen stiffness measurements during recompensation in patients with acutely decompensated liver cirrhosis: preliminary findings of a pilot study - Gülcicegi, Dilan Elcin; Hannemann, Jonathan; Bürger, Martin; Allo, Gabriel; Dittmann, Eva; Martin, Anna; Jaspers, Natalie; Holzapfel, Bianca; Chon, Seung-Hun; Lang, Sonja; Goeser, Tobias; Steffen, Hans-Michael; et al. (Frontiers in Medicine, 2024)
Acute decompensation (AD) in patients with liver cirrhosis is associated with a dramatic deterioration in prognosis. Immediate initiation of appropriate recompensation measures is essential to improve patient's outcome, although objective parameters for evaluating the success of recompensation are still lacking. Spleen stiffness measurements (SSM) have emerged as promising non-invasive tool to assess clinically significant portal hypertension (CSPH), which is the main driver of acute decompensation. However, while SSM accurately predicts CSPH and its complication, currently no data are available on its diagnostic performance during recompensation. This pilot-study aimed at evaluating changes in spleen stiffness following the initiation of recompensation measures in cirrhotic patients hospitalized due to AD.In this prospective pilot-study, 60 patients with cirrhosis showing AD were included liver stiffness measurements (LSM) and SSM on admission day with repetitive SSM on day 3 and 5, respectively, during recompensation measures. A cohort of patients (n=10) with compensated cirrhosis served as control.Results: 36 data sets from the originally enrolled 60 patients were eligible for final analysis. On admission, patients with AD revealed a significantly increased spleen stiffness compared to the control group (70.51 vs. 29.06 kPa, p<0.0001). Following the initiation of recompensation measures SSM revealed a significant reduction in spleen stiffness compared to the baseline assessment on day 3 (-18.5 kPa, -21.53%; p=0.0002) with no further decrease on day 5 (-17.63 kPa, -21.23%; p=0.0326).Repetitive SSM seems to be a useful non-invasive clinical marker to assess the effectiveness of recompensation measures in cirrhotic patients with AD.